Knowledge Management Impact On Corporate Entrepreneurship In IT Industry In Iran - Soleimani, Hamed (2011)
This research aims to explore the idea and provide an answer for the main goal of this study which is to measure knowledge management impact on corporate entrepreneurship in IT industry in Iran. The primary data required to conduct the research was obtained through questionnaire distribution in small, medium, large IT firms or departments through the country.